Effect of well-being and thermal comfort on livestock production: a literature review (Research, Society and Development, 2020)
This article aims to define animal welfare, treat thermal comfort within the context of animal welfare and determine a parameter of the relationship between bovine thermal comfort and weight gain. The bibliographic review methodology was used, where this type of research is developed based on material already prepared, consisting mainly of books and scientific articles. As a result, the average percentage of weight differences of animals with and without access to shade, was obtained as the parameter of relation between animal weight gain and thermal comfort, which was -9.74%. It was concluded that it is possible to admit, then, that the animal that has access to the shade during the day, produces about 10% (9.74%) more meat (beef cattle) than the animals under heat stress, exposed in the sun all day.